Certified Kubernetes Administrator (CKA) Exam Guide Validate Your Knowledge of Kubernetes and Implement It in a Real-Life Production Environment - Qin, Mélony (Packt Publishing, Limited, 2022)
Develop a deep understanding of Kubernetes and the cloud native ecosystem, and pass the CKA exam with confidence with this end-to-end study guide Key Features Get to grips with the core concepts of Kubernetes API primitives Deploy, configure, manage, and troubleshoot Kubernetes clusters Cement your credibility in the job market by becoming a Certified Kubernetes Administrator Book Description Kubernetes is the most popular container orchestration tool in the industry. The Kubernetes Administrator certification will help you establish your credibility and enable you to efficiently support the business growth of individual organizations with the help of this open source platform. The book begins by introducing you to Kubernetes architecture and the core concepts of Kubernetes. You'll then get to grips with the main Kubernetes API primitives, before diving into cluster installation, configuration, and management. Moving ahead, you'll explore different approaches while maintaining the Kubernetes cluster, perform upgrades for the Kubernetes cluster, as well as backup and restore etcd. As you advance, you'll deploy and manage workloads on Kubernetes and work with storage for Kubernetes stateful workloads with the help of practical scenarios. You'll also delve into managing the security of Kubernetes applications and understand how different components in Kubernetes communicate with each other and with other applications. The concluding chapters will show you how to troubleshoot cluster- and application-level logging and monitoring, cluster components, and applications in Kubernetes. By the end of this Kubernetes book, you'll be fully prepared to pass the CKA exam and gain practical knowledge that can be applied in your day-to-day work. What you will learn Understand the fundamentals of Kubernetes and its tools Get hands-on experience in installing and configuring Kubernetes clusters Manage Kubernetes clusters and deployed workloads with ease Get up and running with Kubernetes networking and storage Manage the security of applications deployed on Kubernetes Find out how to monitor, log, and troubleshoot Kubernetes clusters and apps among others Who this book is for This book is for application developers, DevOps engineers, data engineers, and cloud architects who want to pass the CKA exam and certify their Kubernetes Administrator skills in the market. Basic knowledge of Kubernetes is recommended to get the most out of this book.